Soil governance as a requirement for agricultural land conservation: a historical overview - Santos Telles, Tiago; Moraes de Cesare Barbosa, Graziela; Henrique Merten, Gustavo; Pellini, Tiago; Jonas Didoné, Elizeu; de Fátima Guimarães, Maria (Revista Ciência Agronômica, 2023)
This study is a historical overview of land governance initiatives implemented in Parana state, Brazil, since the 1970s, ranging from the work carried out by research institutes to government-sponsored programs. These initiatives encouraged the development of technologies and farmers’ widespread adoption of conservation practices. Furthermore, they highlight the factors that brought soil and water conservation to the forefront in discussions on agriculture. This bibliographic review was based on information in research papers and programs developed in Parana. We show that extensive work on management planning and natural resource conservation was undertaken in Parana to strengthen soil governance. The initiatives implemented in watersheds and the development of the no-tillage system represent considerable achievements. However, it was not always that straightforward. As time progressed, the false perception – mainly among farmers – that the erosion problem had been solved led many farmers to neglect soil conservation practices, and in some cases, to abandon agricultural terracing, contour farming, and crop rotation. This resulted in a resurgence of problems related to environmental degradation, aggravating erosion and causing losses of soil and water, with the concomitant environmental damage. In this regard, we describe the means deployed in a new strategy to stimulate a resurgence of effective soil governance based on public policies and public-private partnerships to promote soil and water conservation.